Piet Go, Ensiklik Rerum Novarum dan Quadragesimo Anno dan Transformasi Moral Millenial - Godlif Sianipar (Litbang STFT Widya Sasana Malang, 2021)
This research discusses about moral problems that are occuring daily in the society and the Church as pointed out by Piet Go Twan An. Those moral problems are the problems created by firstly the Indonesian Marriage Law; secondly the problem of pastoral care among the priests should be reformed to suit inter-personal relations with God’s people so that the Church’s missions are recived affectively and efficiently; thirdly the problem of corruption in the government and the needs for the Church to be pro-active in eradicating corruptions; and the last point is the problem of homosexuality or LGBT issues. Solution is offered by moral transforming among its people (the faithful and the people) namely personal ethic transformation based on the Papal Encyclic Rerum Novarum and Quadragesimo Anno. This research is to address the question of how much personal moral transformation is needed to overcome moral problems in the society. The samples of this research are 895 people of Christians and Cahtolics in Medan. By using the Analysis Factor and SEM methods, it is predicted that there will be an increase of 0.08 on the transformation of personal morals if there is an effort of 0.28 points to improve the morals of the faithful and the people of Medan.